Molecular Detection of hlyA Gene from Escherichia coli hemolytic isolated from Intestinal and Urinary Tract infections - Raid Razzaq Ojaimi (Journal of Global Pharma Technology, 2016)
An Intestinal and Urinary tract infection is a common clinical problem worldwide. In this study 76 isolates Escherichia coli were isolated from midstream urine specimens only 30 isolates show ability to hemolysis, and 80 isolated Escherichia coli from diarrhea specimens only 10 isolates show ability to hemolysis. In this study, hlyA gene responsible for hemolysin production were detected, from fifteen clinical isolate distributed on 10 isolates of urine and 5 isolates of diarrhea of E.coli collected from 40 isolates for hemolysin produced by using PCR techniques. hlyA gene was present in all isolates. Keywords: Hlya, Escherichia coli, Hemolysin.